Pengembangan Media Pembelajaran Berbasis Android Pada Mata Kuliah Sistem Operasi di Universitas Hamzanwadi - Mustapid Amna; Rasyid Hardi Wirasasmita; Ahmad Fathoni (Jurnal Pendidikan Informatika (EDUMATIC), 2018)
The purpose of this study is to find out: (1) Results of Development of Android-Based Learning Media At the Course of Operation System Semester II Informatics Education Study Program Hamzanwadi University, (2) the level of feasibility of learning media developed. This research is a Research and Development research with ADDIE development model, which are: Analisys, Design, Development, Implementation and Evaluation. Instrument used in this research is lift (quisioner) by using likert scale. Sources of research data are 2 media experts, 2 material experts, and 30 students of study program of informatics education. The results of this study are the Development of Android-Based Learning Media with the display of a list of menu pages, Profile, Material, Submenu Matter, Video, submenu Video, RPS, Instructions. Feasibility test results of Media Expert reviewed from 2 aspects included into the category Very Eligible (90%). And the test results from the Master of Materials into the category of Very Eligible (86%). Based on the response of media usage by 30 Students of Second Semester of Informatics Education Study Program is categorized as feasible (78